2005
DOI: 10.1002/ajmg.a.30771
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive behaviors and risk factors among the genetic subtypes of Prader–Willi syndrome

Abstract: Maladaptive behaviors among 65 people with Prader-Willi syndrome were assessed using the Reiss Screen for maladaptive behaviors. Young adults in their twenties were more likely to display aggressive behavior than adolescents and older adults. Differences in maladaptive behaviors between the typical deletion and uniparental disomy (UPD) subtypes were evaluated. The typical deletion subtype had higher self-injury and stealing scores than the UPD subtype. Subject characteristics were differentially related to mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 24 publications
9
84
2
Order By: Relevance
“…However, at this time, CMA is more expensive to have more compulsions and poorer adaptive behavior, intellectual ability, and academic achievement than those with type 2 deletions (BP2-BP3) deletions. 131,132 Two other studies found much less clinically significant differences between individuals with these two deletion types. 133,134 diAGnOstic testinG DNA methylation analysis is the most efficient way to start the genetic workup if PWS is suspected clinically (Figure 5 and Table 3).…”
Section: Paternal Deletionmentioning
confidence: 95%
“…However, at this time, CMA is more expensive to have more compulsions and poorer adaptive behavior, intellectual ability, and academic achievement than those with type 2 deletions (BP2-BP3) deletions. 131,132 Two other studies found much less clinically significant differences between individuals with these two deletion types. 133,134 diAGnOstic testinG DNA methylation analysis is the most efficient way to start the genetic workup if PWS is suspected clinically (Figure 5 and Table 3).…”
Section: Paternal Deletionmentioning
confidence: 95%
“…Additional contextual data also suggest that this variant is pathogenic. This region is deleted in some individuals with Prader-Willi and Angelman syndromes, and there is evidence that individuals with Prader-Willi or Angelman syndrome that carry the larger deletion (BP1-BP3) are more severely affected than those with only deletions of the critical interval (Butler et al 2004;Hartley et al 2005;Sahoo et al 2006). Furthermore, deletions of this region were found more frequently in individuals with schizophrenia compared to controls in two independent studies Kirov et al 2009).…”
Section: Efficient Targeted Detection Of Rare Cnvsmentioning
confidence: 99%
“…16 43 Hartley and colleagues indicated people with Type I deletion had significantly higher Reiss depression (physical signs) scores than people with Type II deletion. 42 In addition, Zarcone and colleagues found more washing/cleaning compulsions in those with Type I deletions and more rereading and rewriting compulsions in those with Type II deletions. 44 However, these results have yet to be replicated.…”
Section: Behavior and Cognitionmentioning
confidence: 98%
“…66 In fact, Hartley and colleagues 42 found individuals with PWS aged 20-29 years had significantly higher aggressive behavior scores than those aged 12-19 years and 30-45 years. The combination of adolescence and early adulthood being a period of emotional lability, independence seeking, and a period where difficulties with socialization abound as peers mature more rapidly makes this time especially challenging.…”
Section: Behavioral Managementmentioning
confidence: 99%